Analysis of the Influence of the Ability to Prepare Financial Reports, Financial Literacy and Financial Inclusion on the Financial Performance of MSMES - Hutabarat, Metyria Imelda; Widiyastuti, Tetty; Duffin; Ervina, Nelly (Yayasan Ilomata, 2024)
Improving community welfare can be achieved by improving the performance of small and medium scale businesses because MSMEs can be a forum for the majority of society to meet their needs. This research aims to analyze the influence of the ability to prepare financial reports, financial literacy and financial inclusion on the financial performance of MSMES. This research was descriptive research. This research is classified as quantitative research by utilizing data obtained from 100 respondents consisting of MSME units. The data collection stage was carried out with instruments in the form of questionnaires and tests. The results of the analysis show that the ability to prepare financial reports, financial literacy, and financial inclusion partially have a positive and significant influence on the financial performance of MSMEs. Another interesting finding is that the analysis carried out simultaneously shows that the ability to prepare financial reports, financial literacy, and financial inclusion have simultaneously significant positive influence on the financial performance of MSMEs in Medan City. The results of this research are very important for assessing the situation and future prospects of MSMEs in this country. The implications of this research encourage the development of strategies and policies that can improve the ability to prepare financial reports, optimize financial literacy, financial inclusion and encourage MSME financial management behavior so that it can improve the financial performance of MSMEs, which in turn will improve the welfare and sustainable growth of the MSME sector.